2018
DOI: 10.1111/nmo.13431
|View full text |Cite
|
Sign up to set email alerts
|

The central effects of buspirone on abdominal pain in rats

Abstract: Buspirone exerts complex biphasic action on the pain-related VLM neuron activity inversely depending on dose. The final effect of buspirone depends on the functional balance between of activation the pre- and postsynaptic 5-HT Rs in mediating pain control networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…The buspirone‐produced reduction in the CRD‐evoked excitation of the CVLM neurons and blood pressure response to CRD that we observed in healthy control animals is in accordance with our previous findings, demonstrating similar manifestations of visceral antinociceptive properties of the drug in normal conditions (Panteleev et al, 2018, 2021). In turn, the suppressive action of the compound on the visceromotor reactions to CRD, we showed in the control rats, is in agreement with our previous study in dogs (Lyubashina et al, 2017) and other studies reporting analgesic effect of buspirone and another 5‐HT1A agonist, 8‐OH‐DPAT in conscious animals (Abdel Salam & Baiuomy, 2007; Danzebrink & Gebhart, 1991; Galeotti et al, 1997; Korzeniewska‐Rybicka & Płaźnik, 2001; Rouzade et al, 1998; Sivarao et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The buspirone‐produced reduction in the CRD‐evoked excitation of the CVLM neurons and blood pressure response to CRD that we observed in healthy control animals is in accordance with our previous findings, demonstrating similar manifestations of visceral antinociceptive properties of the drug in normal conditions (Panteleev et al, 2018, 2021). In turn, the suppressive action of the compound on the visceromotor reactions to CRD, we showed in the control rats, is in agreement with our previous study in dogs (Lyubashina et al, 2017) and other studies reporting analgesic effect of buspirone and another 5‐HT1A agonist, 8‐OH‐DPAT in conscious animals (Abdel Salam & Baiuomy, 2007; Danzebrink & Gebhart, 1991; Galeotti et al, 1997; Korzeniewska‐Rybicka & Płaźnik, 2001; Rouzade et al, 1998; Sivarao et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…In particular, 5-HT1A agonists have been shown to produce antinociceptive effects in various visceral pain models in rodents (Abdel Salam & Baiuomy, 2007;Danzebrink & Gebhart, 1991;Galeotti et al, 1997;Korzeniewska-Rybicka & Płaźnik, 2001;Rouzade et al, 1998;Sivarao et al, 2004). In line with these findings, we previously demonstrated that buspirone, a partial agonist of 5-HT1A receptors, dose dependently inhibited visceromotor reactions and medullary neuronal responses to noxious colorectal distension in healthy awake dogs and anesthetized rats Panteleev et al, 2018Panteleev et al, , 2021. However, in other studies 5-HT1A receptor activation led to pronociceptive effect (Coelho et al, 2001;Mickle et al, 2012), whereas 5-HT1A antagonists attenuated visceral pain perception (Coelho et al, 1998;Lindström et al, 2009).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the ACC, there are many subtypes of serotonin receptors. According to previous reports, 5-HT1A and 5-HT7 receptors play important roles in pain conditions (15,30,47). Therefore, to further explore ACC downstream targets for increased release of serotonin induced by exercise, we conducted further studies on 5-HT1A and 5-HT7 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Several published controlled studies have evaluated amitriptyline, citalopram, duloxetine and other antidepressants in adults, which generally support efficacy in both neuropathic and non-neuropathic pain, with the effect being greater for tricyclic antidepressants and serotonin-norepinephrine reuptake inhibitors than serotonin-specific reuptake inhibitors. 29 , 30 For buspirone, although preclinical studies demonstrate antinociceptive effects, 31 , 32 the clinical evidence supporting benefit is weak. 33 In our study, we also observed that without buspirone, pooled effect was greater and more significant.…”
Section: Discussionmentioning
confidence: 99%